2019
DOI: 10.1111/are.14385
|View full text |Cite
|
Sign up to set email alerts
|

Substituting fishmeal with extruded soybean meal in diets did not affect the growth performance, hepatic enzyme activities, but hypoxia tolerance of Dolly Varden (Salvelinus malma) juveniles

Abstract: Extruded soybean meal (ESBM) showed increased digestibility of crude protein, amino acids and fat, better oil retention capacities, attenuated anti‐nutrient factor effects and improved its nutritive value compared with raw soybean meal, indicating a promising application prospects for ESBM in fish culture. This study aimed to evaluate the effects of substituting fishmeal with ESBM on growth performance, hepatic antioxidant capacity and the resistance to hypoxia stress on juvenile Dolly Varden (Salvelinus malma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…This explains why R. lagowskii had a higher acceptance of ESBM compared with SBM in our study. And the same results were found in Asian Swamp Eel Monopterus albus (Zhang et al 2015), Dolly Varden (Meng et al 2020), and Rainbow Trout (Santizo‐Taan et al 2020). It is worth noting that the extrusion process of ESBM cannot effectively remove heat‐stable antinutritional factors (mainly including soya‐saponins, soy antigen protein, phytic acid, isoflavone, oligosaccharide, tannin) or optimize the composition of amino acids profile (Zhang et al 2015).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This explains why R. lagowskii had a higher acceptance of ESBM compared with SBM in our study. And the same results were found in Asian Swamp Eel Monopterus albus (Zhang et al 2015), Dolly Varden (Meng et al 2020), and Rainbow Trout (Santizo‐Taan et al 2020). It is worth noting that the extrusion process of ESBM cannot effectively remove heat‐stable antinutritional factors (mainly including soya‐saponins, soy antigen protein, phytic acid, isoflavone, oligosaccharide, tannin) or optimize the composition of amino acids profile (Zhang et al 2015).…”
Section: Discussionsupporting
confidence: 54%
“…Extrusion technology could effectively reduce the antinutritional factor content in SBM and increase the free amino acid content (Pongmaneerat and Watanabe 1993; Berenti et al 2021). Studies on broiler chicks and Dolly Varden have revealed that ESBM increased the digestibility of crude protein, amino acids, and fat and weakened the effect of antinutritional factors compared with SBM (Jahanian and Rasouli 2016; Meng et al 2020). These studies show that ESBM has a good application prospect in the feed industry and also partly explain why ESBM has less effect on muscle crude protein content of R. lagowskii compared with SBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity of utilizing soybean meal as a dietary fishmeal substitute has been evaluated in a wide range of carnivorous fish species, such as giant snakehead Channa micropeltes (Hien et al, 2015), Japanese seabass Lateolabrax japonicas (Zhang et al, 2016, 2018), European sea bass Dicentrarchus labrax (Bonvini et al, 2017), Dolly Varden Salvelinus malma (Meng et al, 2019), Asian seabass Lates calcarifer (Ma et al, 2019) and rainbow trout Oncorhynchus mykiss (Yeşilayer & Kaymak, 2020). Early study suggested that average final weight of largemouth bass declined significantly when reducing dirtary fishmeal level from 300 g/kg to 150 g/kg, with soybean meal used as a fishmeal substitute (Tidwell et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among the plant ingredients used in aqua‐feed, soybean has been demonstrated as an excellent protein source due to its high protein digestibility, relative balance of amino acids, huge global production and reasonable market price (Metts et al, 2011; Wang et al, 2006). The potential of replacing fishmeal with soybean‐derived ingredients (soybean meal, soy protein concentrate and isolated soy protein) in diets for carnivorous fish species has been intensively evaluated (Biswas et al, 2019; Bonvini et al, 2017; Hossain et al, 2019; Ma et al, 2019; Meng et al, 2019; Novriadi et al, 2017; Yaghoubi et al, 2016; Yeşilayer & Kaymak, 2020; Zhang et al, 2016, 2018). And results from these studies suggested that fishmeal replacement level by soybean‐derived ingredients varies among different fish species.…”
Section: Introductionmentioning
confidence: 99%